In-vivo study of oleic acid and tween-80 on patch transdermal A.paniculata as anti-diabetic - Wahyuningsih, Iis; Fadilah, Nur Aini; Widyaningsih, Wahyu (Universitas Ahmad Dahlan, 2024)
Sambiloto (Andrographis paniculata) has been known empirically as a plant that has benefits as a traditional antidiabetic Javanese medicine to treat diabetes mellitus (DM). The main compound contained in sambiloto is andrographolide which has a hypoglycemia effect. Andrographolide has low solubility in water and poor bioavailability due to biotransformation by P-glycoprotein in the intestinal tract which causes andrographolide to metabolize more quickly in the duodenum and jejunum. To overcome this extract ethanol of sambiloto (EES) formulated to patch transdermal. Enhancers can affect the characteristics of transdermal patch preparations which affect the pharmacological activity of transdermal patch preparations. The critical point of transdermal patch preparation is the selection of enhancers which is one of the compounds to increase the penetration of active substances in the skin by disrupting the permeability of the stratum corneum. The aim of this research is to determine the effect of variations in the combination of oleic acid and tween 80 as an enhancer on the physical characteristics of EES patches.The methods of extraction sambiloto use soxhetation with ethanol 96% as solvent. The formulation of EES patch transdermal using solvent casting technique with various concentration enhancer tween-80 and oleic acid. This research was conducted by making 3 formulas, where F1 (1:1), F2 (1:3) and F3 (1:3). The evaluations include weight uniformity, thickness, water content, pH and folding endurance of the patch. The result of visual appearance the patch EES has a dark green with aroma specific of EES. The characteristics of EES transdermal patches were affected by the ratio of tween-80 and oleic acid as the enhancers. The combination of oleic acid and tween 80 as a permeation enhancer has an influence on physical characteristics (weight and thickness) of EES patches.